Administrative Management Evaluation Of Bengkulu City Transportation Agency In The Management Of Traffic Signs And Road Markings - Saraswati, Putri dewi; Saputra , Harius Eko; IS , Tuti Handayani (CV. Utami, 2025)
This research aims to analyze the effectiveness of the Bengkulu City Transportation Agency’s management using Henry Fayol’s Management Theory, which includes planning, organizing, directing, coordinating, and controlling functions. The study employed a descriptive qualitative method with an empirical approach through interviews, field observations, and reviews of official documents. The findings show that planning functions are based on field surveys and accident-prone area identification but are not yet integrated into real-time data-based information systems and are hindered by budget limitations. The organizing function has a clear regulatory basis but is constrained by a lack of technical personnel, limited training, and insufficient equipment, causing reliance on third parties. The directing function is carried out through assignment letters and verbal instructions but lacks written SOPs, leading to inconsistencies in implementation. Internal and external coordination is not yet optimal due to the absence of digital management systems. The controlling function is the weakest aspect, as monitoring remains reactive without routine inspections and technological support. Overall, the Bengkulu City Transportation Agency’s management in handling traffic signs and road markings has attempted to apply management principles but has not been optimally implemented. Management reforms through system digitalization, human resource enhancement, equipment updates, and accident-priority data-based planning are urgently needed to improve traffic service effectiveness.